Mechanisms of vascular damage in obstructive sleep apnea - Kohler, M; Stradling, JR (2010)
Obstructive sleep apnea (OSA) is characterized by repetitive apnea-hypopnea cycles during sleep, which are associated with oxygen desaturation and sleep disruption. Up to 30% of the adult population in Western countries are thought to be affected by asymptomatic OSA and approximately 2-4% by symptomatic OSA (also known as obstructive sleep apnea syndrome, or OSAS). Controlled trials have demonstrated that OSAS causes hypertension and prospective epidemiological studies have indicated that OSAS might be an independent risk factor for stroke and myocardial ischemia. Three biological mechanisms are thought to underpin the association of OSA with endothelial dysfunction and arterial disease: intermittent hypoxia leading to increased oxidative stress, systemic inflammation, and sympathetic activity; intrathoracic pressure changes leading to excessive mechanical stress on the heart and large artery walls; and arousal-induced reflex sympathetic activation with resultant repetitive blood-pressure rises. More clinical interventional trials are needed to determine the magnitude of the effect OSA has on cardiovascular damage and to enable a comparison with conventional vascular risk factors. © 2010 Macmillan Publishers Limited. All rights reserved.